A Novel Branched DNA-Based Flowcytometric Method for Single-Cell Characterization of Gene Therapy Products and Expression of Therapeutic Genes - Garcia-Perez, Laura; van Eggermond, Marja C.J.A.; Maietta, Elisa; van der Hoorn, Marie-Louise P.; Pike-Overzet, Karin; Staal, Frank J. T. (Frontiers in Immunology, 2021)
Many preclinical and clinical studies of hematopoietic stem cell-based gene therapy (GT) are based on the use of lentiviruses as the vector of choice. Assessment of the vector titer and transduction efficiency of the cell product are critical for these studies. Efficacy and safety of the modified cell product are commonly determined by assessing the vector copy number (VCN) using qPCR. This optimized and well-established method in the GT field is however based upon bulk population averages which can lead to misinterpretation of the actual VCN of the transduced cells. Therefore, we introduce here a single cell-based method that allows to unmask cellular heterogeneity in the GT product, even when antibodies are not available. We use Invitrogen’s PrimeFlow™ RNA Assay, a flow cytometry-based assay, with customized probes to detect transgenes of interest to determine transduction efficiency, promoter strength and cellular heterogeneity on murine and human stem cells. Indeed, this assay show good specificity and sensitivity to detect the transgenes. We observed high correlation of the standard VCN, obtained by qPCR, with the percentage of transduced cells expressing the transgene and/or their MFI. Differences in promoter strengths can readily be detected. Hence, we show a customizable method that allows to determine the “real” VCN of the actual transduced cells in a GT product, being adaptable to other therapeutic genes for which antibodies are not available or too cumbersome for routine flow cytometry. The method also allows co-staining of surface markers to analyze differential transduction efficiencies in subpopulations of target cells